O TRABALHO DOCENTE NO ENSINO SUPERIOR: DESAFIOS FRENTE À GERAÇÃO Y - Ines Cristina Giometti; Alba Regina Azevedo Arana; Elisangela Bulla Ikeshoji (Universidade do Oeste Paulista, 2015)
With the political, economic, social and technological changes arise generations that share the characteristics of the time and context in which they lived. The generation that now attends college banks is known as Generation Y, who grew already connected to the internet. The younger generation are often sighted, impatient, do not deal well with criticism, want a steady return and are less committed. Facing a different generation in a classroom, which is used to the prompt information to the internet, always connected to a mobile and easily get bored with the traditional way of teaching is a challenge to be faced by teachers today. Therefore, the aim of this paper is to present a reflection on the pedagogical challenges that college teachers face in their practices before the formation of a new generation (Generation Y). This paper will present the main features of different generations; reference works featuring Generation Y; analyze the importance of teaching in higher education and reflect on the possibilities of teaching practices that best meets the needs of Generation Y in the classroom. Approach used for survey and preparation of the data was based on literature review, scientific books and articles. The main results show that for this generation of college students, we must give priority to participation and student 171 Colloquium Humanarum, Presidente Prudente, v. 12, n. 1, p.170-192, jan/mar 2015. DOI: 10.5747/ch.2015.v12.n1.h001X involvement in the process of teaching and learning, seeking educational alternatives such as problem solving, group work, development of creative projects (models, movies, theaters and other gender), and the use of multimedia tools (for greater virtual communication).